Dietary effects of supplementation of cattle stick Carpolobia lutea leaf on growth and reproductive indices of male and female Clarias gariepinus broodstock - Sunday Emmanuel Olusola; Charles Abiodun Aladegboye; Folasade Damilola Amulejoye; Abolupe Oluyemi Ayanboye (Aceh Journal of Animal Science, 2022)
Males and females broodstock of Clarias gariepinus (mean weight, 884.00±2.83g) were subjected to dietary supplementation of Cattle Stick (Carpolobia lutea) Leaf (CSL) at different inclusion levels of 0 (control), 0.5, 1.0 and 2.0% to evaluate the efficacy of the plant for growth performance and fertility enhancer.  Clarias gariepinus broodstock (96) were allocated into 12 experimental fibre tanks at 8 fish per tank (4 males and 4 females) fed 40% crude protein at 3% body weight twice daily for 56 days. Each treatment was done in triplicate.  Biological evaluation and reproductive indices were measured. There was significant difference (P0.05) in weight gained by fish fed experimental diets.  Fish fed experimental diets containing CSL showed significantly higher (P 0.05) reproductive indices compared to the control diet. 0.5% inclusion level of CSL showed better performance in term of growth performance and reproductive indices and may be considered to be the best tolerance inclusion level for growth performance and fertility enhancer. The results of the study indicate that incorporating Cattle stick leaf diets in fish feed at 0.5% may have the potential for growth performance and fertility-enhancing agent in male and female C. gariepinus broodstock.Keywords: Clarias gariepinus, Carpolobia lutea leaf Growth, Reproductive indices, Broodstock